Use of ticagrelor in human pregnancy, the first experience. (25th November 2015) - Verbruggen, Marjan; Mannaerts, Dominique; Muys, Joke; Jacquemyn, Yves
Abstract : Ticagrelor was daily administered throughout pregnancy to a 37-year-old pregnant woman until 36 weeks of gestation. The patient, with Behçet disease, suffered from a non-ST elevation myocardial infarction 4 months before conception, possibly related to hypertension and tobacco abuse. Pregnancy and postpartum periods were uneventful. She delivered a healthy but small-for-gestational-age term neonate.